(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2018)
Objective: To translate and adapt the “Perineal Assessment Tool” for Brazilian culture. Method: A methodological study constituted by the following stages: translation, synthesis, back-translation, analysis by a judges committee and pre-test. Results: The evaluation of produced versions was realized by a committee of fi ve judges who analyzed the semantics, idiomatic and cultural equivalence. A cultural validation index equal to or greater than 0.91 was obtained. A pre-test was performed, applying the pre-final version to 37 nurses, with the purpose to evaluate the understanding and relevance through the application of an instrument elaborated based on the Likert analysis. An average of 4.6 was obtained. Conclusion: Cultural adaptation of the instrument “Perineal Assessment Tool” performed in a satisfactory way, however, it is necessary to evaluate the psychometric properties, already in the process of development.